An Analysis Of Obstacles And Teachers’ Challenges In Teaching Speaking At Sman 1 Batulayar - Tawali Tawali; Jumadil Jumadil (Lembaga Penelitian dan Pendidikan Mandala, 2026)
WThis study aimed to analyze the challenges and obstacles that teacher faced in teaching speaking at SMAN 1 BATULAYAR. The researcher used a qualitative method. The subjects of this study were two English teachers at SMAN 1 BATULAYAR, and the object of the study was the challenges and obstacles faced by the teachers in teaching speaking. The data analysis used in this study was data reduction, data display, and conclusion and verification. The results showed several main challenges: students passivity, limited vocabulary, lack of motivation, fear of making mistakes, lack of resource, and noisy class. In addition, teachers faced internal obstacles such as insufficient training in teaching speaking, as well as external obstacles, including limited teaching facilities, large class size, and limited time for speaking practice. These problems made it difficult for students to participate actively in speaking activities. The study concluded that teachers needed to implement better strategies to increase students’ motivation, and active participation in speaking. It was also recommended that the school improve its learning facilities.